Climate-Smart Agriculture: Scientists' perspectives - Verhagen, J; Vellinga, Theun V.; Neijenhuis, F; Jarvis, Tu; Jackson, L.; Caron, P.; Torquebiau, Emmanuel F.; Lipper, Leslie; Fernandes, E; Entsua-Mensah, R.E.M.; Vermeulen, Sonja J. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
Climate Smart Agriculture is an integrated approach to achieve food security in the face of climate change, while also mitigating climate change and contribute to other development goals. Leading scientists share views on what is Climate-Smart Agriculture and how to make it work. This brief was an output of the 2nd Global Science Conference on Climate-Smart Agriculture at UC Davis.